2021
DOI: 10.4266/acc.2021.00234
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-induced cardiomyopathy is associated with higher mortality rates in patients with sepsis

Abstract: Septic cardiomyopathy and mortalityBackground: Patients with sepsis are at risk for developing sepsis-induced cardiomyopathy (SIC).Previous studies offer inconsistent results regarding the association of SIC and mortality. This study sought to assess whether SIC is linked to mortality in patients with sepsis and to evaluate predictors of the development of SIC.Methods: In this retrospective study, patients admitted to the medical intensive care unit with a diagnosis of sepsis in the absence of acute coronary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Nowadays, SICM diagnosis does not count with a golden standard, which results in the use of different diagnostic criteria among researchers and a wide variation in the SICM incidence reports. In our study, this incidence, for all three diagnostic criteria, was about 20-40%, and thus similar to most literature reports 11,19,28 . The incidence of SICM, based on the LVEF criteria, was signi cantly lower than that based on GLS or TMAD, which might be related to the superiority of STE in detecting subclinical cardiac insu ciency 29 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nowadays, SICM diagnosis does not count with a golden standard, which results in the use of different diagnostic criteria among researchers and a wide variation in the SICM incidence reports. In our study, this incidence, for all three diagnostic criteria, was about 20-40%, and thus similar to most literature reports 11,19,28 . The incidence of SICM, based on the LVEF criteria, was signi cantly lower than that based on GLS or TMAD, which might be related to the superiority of STE in detecting subclinical cardiac insu ciency 29 .…”
Section: Discussionsupporting
confidence: 92%
“…Left ventricular ejection fraction (LVEF) is the conventional indicator when evaluating LV systolic function. An LVEF onset of less than 50% is often considered as the diagnostic criteria for SICM [11][12][13][14] . In this regard, speckle tracking echocardiography (STE) is an angle-independent and semi-automatic method for LV strain measurements 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite uncertainties about its precise definition, we defined SICM as LVEF < 50% in this study which was reported in most previous literature [ 28 ]. According to the definition, the SICM incidence in our study was similar to most previous reported studies [ 2 , 16 , 29 ]. Consistent with some previous investigations [ 6 , 7 ], SICM mortality in our study was significantly higher (about 2.5 times) than that of non-SICM patients.…”
Section: Discussionsupporting
confidence: 91%
“…Sepsis-induced cardiomyopathy (SICM), initially described in the 1980s, is generally defined as an acute and reversible cardiac dysfunction that involves decreased left and/or right ventricular systolic and/or diastolic function, left ventricular dilatation, and absence of acute coronary syndrome [ 1 ]. Although there is no formalized or consensus definition, the left ventricular ejection fraction (LVEF) of less than 50% is often considered as indicative of SICM [ 2 5 ] in most literature. SICM is commonly found in patients with sepsis, especially those with septic shock [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the complex hemodynamic profiles may not have been fully quantified and accounted for in most critically ill septic patients [ 40 ]. Besides, the results of the previous studies could be biased due to the lack of adjustment of sepsis severity scores, different types of vasopressors, and other variables [ 2 , 41 ].…”
Section: Discussionmentioning
confidence: 99%